Study of lead-free vacancy ordered double perovskites Cs2TeX6 (X = Cl, Br, I) for solar cells, and renewable energy. (1st September 2022) - Albalawi, Hind; Nazir, Ghazanfar; Younas, Muhammad; Al-Qaisi, Samah; Ashiq, M G B; Alzahrani, Jameelah; Somaily, H H; Morsi, Manal; Ghrib, T
Abstract: Herein, the electronic, optical, mechanical, and transport properties of a double perovskites Cs2 TeX6 (X = Cl, Br, I) are explored with the focus on solar cell and thermoelectric applications by the density functional theory (DFT). The feasibility of structural, thermodynamic, and elastic stabilities is arbitrated by a tolerance factor, formation energy, and elastic constant, respectively. Further, the Poisson and Pugh's ratio display the ductile behavior of studied compounds. From the electronic properties analysis, it is revealed that the bandgap decreases by changing Cl with Br, and I from 2.67 eV to 2.52 eV and 1.73 eV, respectively which in results tune the optical properties from visible to infrared region. The shifting of maximum absorption from visible to infrared region makes them promising materials for solar cell and remote sensing devices. Moreover, various optical parameters including refractive index, reflectivity, and optical loss were also reported. Additionally, the transport characteristics were analyzed by electrical, thermal conductivities, and figure of merit (ZT) versus temperature and chemical potential effect. The ZT increases from Cl to I substitution. At the end, the thermodynamic behavior studied by specific heat capacity, Debye temperature and Hall coefficient was presented. All these characteristics have demonstrated that our studied materials are excellent choice for probing solar cell and renewable energy applications.